MOLECULAR DOCKING AND IN SILICO ANALYSIS OF ARTEMISIA DRACUNCULUS PHYTOCOMPOUNDS FOR MUCIN-1 MODULATION IN FIBROSIS - Waqar Sarmad Khaliq; Sumaira Sharif; G. Mustafa; Iffat Nayila; Riaz Ullah; Asma Irshad; Madeeha Shahzad Lodhi; Syed Ali Raza Shah; Maira Bibi (Journal of Animal and Plant Sciences, 2026)
Liver cancer is a disease that may cause morbidity and mortality all over the world. Liver cancer is responsible for over 700,000 fatalities worldwide each year, and the number is rising daily. Numerous studies have demonstrated that herbal remedies can be used to treat a variety of liver conditions, including cancer. Artemisia dracunculus is used as a medicinal plant because it possesses alkaloids, phenols and flavonoids. In this study, A. dracunculus was extracted using 25 g of powder in 200 mL of ethanol. HPLC analysis of A. dracunculus ethanol extract showed the presence of different compounds. The identified lead compounds were docked against liver cancer protein mucin-1 (MUC1) to check their binding affinity. The compounds including myricetin, 1,2,3-oxadiazole, bicyclo [3.3.1] non-2-en-9-ol, and 6-methoxy-2-aminopyridinamine showed good binding energies with docking scores of –6.3, –6.7, –5.7, and –3.8 kcal/mol, respectively. Molecular dynamic simulations were performed to check the structural conformational changes due to the binding affinity of ligands to mucin-1. Various kinds of interactions between mucin-1 and ligand compounds such as bicyclo[3.3.1]non-2-en-9-ol, myricetin and1,2,3-Oxadiazole were demonstrated in this study. Some residues of mucin-1 also developed bonding contacts and produced hydrogen bonds for 60-80 % of the simulation. There are also some intramolecular hydrogen bonds present to indicate the stability of ligands. These compounds were found to have potential activity in curing liver cancer due to their best binding values and simulation patterns. These findings will help researchers to explore more about anticancer compounds from natural sources and new drug design and development. In vitro and in vivo models of liver cancer that overexpress MUC1 might be used to assess the pharmacokinetics, and absorption of promising drug candidates. In the future, these discoveries might aid researchers in creating novel therapeutic candidates to combat liver cancer.
Keywords: A. dracunculus; flavonoids; liver-cancer; mucin-1; molecular docking; molecular dynamic simulation